Genome-wide identification of sucrose non-fermenting-1-related protein kinase genes in maize and their responses to abiotic stresses - Feng, Xue; Meng, Quan; Zeng, Jianbin; Yu, Qian; Xu, Dengan; Dai, Xuehuan; Ge, Lei; Ma, Wujun; Liu, Wenxing (Frontiers in Plant Science, 2022)
Introduction Protein kinases play an important role in plants in response to environmental changes through signal transduction. As a large family of protein kinases, sucrose non-fermenting-1 (SNF1)-related kinases (SnRKs) were found and functionally verified in many plants. Nevertheless, little is known about the SnRK family of Zea mays. Methods Evolutionary relationships, chromosome locations, gene structures, conserved motifs, and cis-elements in promoter regions were systematically analyzed. Besides, tissue-specific and stress-induced expression patterns of ZmSnRKs were determined. Finally, functional regulatory networks between ZmSnRKs and other proteins or miRNAs were constructed. Results and Discussion In total, 60 SnRK genes located on 10 chromosomes were discovered in maize. ZmSnRKs were classified into three subfamilies (ZmSnRK1, ZmSnRK2, and ZmSnRK3), consisting of 4, 14, and 42 genes, respectively. Gene structure analysis showed that 33 of the 42 ZmSnRK3 genes contained only one exon. Most ZmSnRK genes contained at least one ABRE, MBS, and LTR cis-element and a few ZmSnRK genes had AuxRR-core, P-box, MBSI, and SARE ciselements in their promoter regions. The Ka:Ks ratio of 22 paralogous ZmSnRK gene pairs revealed that the ZmSnRK gene family had experienced a purifying selection. Meanwhile, we analyzed the expression profiles of ZmSnRKs, and they exhibited significant differences in various tissues and abiotic stresses. In addition, A total of eight ZmPP2Cs, which can interact with ZmSnRK proteins, and 46 miRNAs, which can target 24 ZmSnRKs, were identified. Generally, these results provide valuable information for further function verification of ZmSnRKs, and improve our understanding of the role of ZmSnRKs in the climate resilience of maize.